Hypercapnic Ventilatory Response in the Weaning of Patients with Prolonged Mechanical Ventilation - Chung-Shu Lee; Ning-Hung Chen; Li-Pang Chuang; Chih-Hao Chang; Li-Fu Li; Shih-Wei Lin; Hsiung-Ying Huang (Canadian Respiratory Journal)
Objective. To investigate whether hypercapnic ventilatory response (defined as the ratio of the change in minute ventilation [ΔV˙E] to the change in end-tidal partial pressure of carbon dioxide [ΔPETCO2]) is a predictor of successful weaning in patients with prolonged mechanical ventilation (PMV) and to determine a reference value for clinical use. Methods. A hypercapnic challenge test was performed on 32 PMV subjects (average age: 74.3 years ± 14.9 years). The subjects were divided into two groups (i.e., weaning successes and weaning failures) and their hypercapnic ventilatory responses were compared. Results. PMV subjects had an overall weaning rate of 68.8%. The weaning-success and weaning-failure groups had hypercapnic ventilatory responses (ΔV˙E/ΔPETCO2) of 0.40±0.16 and 0.28±0.12 L/min/mmHg, respectively (P=.036). The area under the receiver operating characteristic curve was 0.716 of the hypercapnic ventilatory response, and the practical hypercapnic ventilatory response cut-off point for successful weaning was 0.265 with 86.4% sensitivity and 50% specificity. Conclusions. PMV subjects who failed weaning had a lower hypercapnic ventilatory response than successfully weaned subjects. However, the prediction capacity of this test, assessed by the area under the receiver operating characteristic (ROC) curve, poorly predicted weaning outcome.